The G protein‐coupled receptor 15 (GPR15) regulates cutaneous immunology by maintaining dendritic epidermal T cells and regulating the skin microbiome. Issue 6 (4th April 2021) - Sezin, Tanya; Jegodzinski, Lina; Meyne, Lisa‐Maria; Gupta, Yask; Mousavi, Sadegh; Ludwig, Ralf J.; Zillikens, Detlef; Sadik, Christian D.
Abstract: The G protein‐coupled receptor 15 (GPR15) regulates homing of different T‐cell populations into the gut, thus, preserving tissue homeostasis. Its potential role in the preservation of homeostasis on other body interfaces, including the skin, is less well understood. We addressed the impact of GPR15 on cutaneous T‐cell populations and the skin microbiome under steady‐state conditions. Genetic deficiency in GPR15 substantially altered the composition of skin‐resident T‐cell populations. Precisely, dendritic epidermal T cells were almost absent in the epidermis of Gpr15 –/– mice. The niche of dendritic epidermal T cells in the epidermis was, instead, populated by αβ TCR + T cells. These changes were associated with shifts in the skin microbiota in Gpr15 –/– mice. Collectively, our results uncover a role of GPR15 in the regulation of the cutaneous immune system and, thus, highlight the receptor as important general regulator of tissue homeostasis of exterior body interfaces. Abstract : GPR15 deficiency alters the composition of cutaneous T cell populations under steady‐state conditions. Dendritic epidermal T cells (DETCs) were reduced in adult Gpr15 −/− mice and their epidermis was instead repopulated by α β TCR + T cells. Furthermore, these changes were associated with shifts in the skin microbiome at steady state.